RTSRE Proceedings 2019
DOI: 10.32374/rtsre.2019.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Attitudinal Gains in Introductory Astronomy Courses

Abstract: Most students do not enroll in introductory astronomy as part of their major; For many, it is the last science course they will ever take. Thus, it has great potential to shape students' attitudes toward STEM fields for the rest of their life. We therefore argue that it is less important, when assessing the effectiveness of introductory astronomy courses, to explore traditional curricular learning gains than to explore the effects that various course components have on this attitude. We describe the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies have found that often the students expect the research experience to be like their college laboratory experience [37,38]. Early scientific research experiences, or experiences with research instrumentation, have been shown to increase students' science self-efficacy as well as their science identity [39][40][41] and help retain students in undergraduate science courses [42][43][44]. Self-efficacy is also a key mediator in identity development [39] and therefore this study developed a specific indicator for astronomy self-efficacy in both knowledge and user instrumentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that often the students expect the research experience to be like their college laboratory experience [37,38]. Early scientific research experiences, or experiences with research instrumentation, have been shown to increase students' science self-efficacy as well as their science identity [39][40][41] and help retain students in undergraduate science courses [42][43][44]. Self-efficacy is also a key mediator in identity development [39] and therefore this study developed a specific indicator for astronomy self-efficacy in both knowledge and user instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid growth of remote telescope technology and programs for students to use this technology [95,96], understanding the impact of these on student outcomes is important. It is a professionally shared, but as yet not robustly tested, opinion that using a researchgrade telescope during a course improves students' selfefficacy and makes them feel like they "can do" astronomy [44,97,98] albeit when executed with careful focus on quality educational design [99]. Promising initial work has shown a correlation between self-efficacy and positive attitudes in robotic telescope undergraduate courses [43], however, positive shifts at the high school level have so far not been measured [100].…”
Section: Introductionmentioning
confidence: 99%